Catalytic Hydrolysis of Perfluorinated Compounds in a Yolk–Shell Micro‐Reactor - Jialin Zheng; Xiaojian Wang; Xin Zi; Hang Zhang; Heping Chen; Evangelina Pensa; Kang Liu; Junwei Fu; Zhang Lin; Liyuan Chai; Emiliano Cortés; Min Liu (Advanced Science)
Abstract Perfluorinated compounds (PFCs) are emerging environmental pollutants characterized by their extreme stability and resistance to degradation. Among them, tetrafluoromethane (CF4) is the simplest and most abundant PFC in the atmosphere. However, the highest C─F bond energy and its highly symmetrical structure make it particularly challenging to decompose. In this work, a yolk–shell Al2O3 micro‐reactor is developed to enhance the catalytic hydrolysis performance of CF4 by creating a local autothermic environment. Finite element simulations predict that the yolk–shell Al2O3 micro‐reactor captures the heat released during the catalytic hydrolysis of CF4, resulting in a local autothermic environment within the yolk–shell structure that is 50 °C higher than the set temperature. The effectiveness of this local autothermic environment is experimentally confirmed by in situ Raman spectroscopy. As a result, the obtained yolk–shell Al2O3 micro‐reactor achieves 100% CF4 conversion at a considerably low temperature of 580 °C for over 150 h, while hollow and solid Al2O3 structures required higher temperatures of 610 and 630 °C, respectively, to achieve the same conversion rate, demonstrating the potential of yolk–shell Al2O3 micro‐reactor to significantly reduce the energy requirements for PFCs degradation and contribute to more sustainable and effective environmental remediation strategies.